2013
DOI: 10.1179/1743132812y.0000000108
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of the human locus coeruleus complex in fetal/neonatal sudden unexplained death

Abstract: The developmental defects found in the locus coeruleus complex in victims of sudden unexplained fetal and infant death imply alterations of the vital activities related to the widespread brain connections arising from this neuronal center, including coordination of the sleep-waking cycle and control of the cardio-respiratory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
1
21
1
1
Order By: Relevance
“…Reduction and/or loss of TH staining in the LC has been reported by Lavezzi et al [25,47], while no differences in TH immunoreactivity in SIDS have been found by other authors [73,74]. …”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Reduction and/or loss of TH staining in the LC has been reported by Lavezzi et al [25,47], while no differences in TH immunoreactivity in SIDS have been found by other authors [73,74]. …”
Section: Discussionmentioning
confidence: 77%
“…Intense TH immunoreactivity in almost all the LC neurons was already observed in the youngest neonate of our sample (aged 25.5 weeks) who belonged to the severe/acute HII group 1. Immunohistochemical studies in human fetal tissues using antibodies against TH and/or dopamine-β-hydroxylase showed that noradrenergic neurons appear in the dorsal pons as early as gestational weeks 5-6 [22,23,24,48], while at birth almost all LC neurons are TH-IR [25], as occurs in the adult [26,27]. The presence of TH immunoreactivity in the adult LC was confirmed by the two adult brain specimens used as positive controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, thalamic lesions in stroke are characterized by ‘suspending' in the drowsy state (extended NREM 1), decreased arousal index and no major REM sleep alterations [58], supposedly accompanied by exaggerated sympathetic activation with preserved parasympathetic drive to the cardiovascular system [59]. The possible approach here could be controlling nondipping BP at bedtime (chronotherapy [60,61]) with angiotensin receptor blockers [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Other staining materials are Lillie for the neuromelanin pigment (28) and Perl’s Prussian blue for iron in oxygen-transporting heme mechanism (29). …”
Section: Stepwise Proceduresmentioning
confidence: 99%